The Salivary Microbiome and Oral Cancer Risk: A Pilot Study in Fanconi Anemia. (March 2017) - Furquim, C.P.; Soares, G.M.S.; Ribeiro, L.L.; Azcarate-Peril, M.A.; Butz, N.; Roach, J.; Moss, K.; Bonfim, C.; Torres-Pereira, C.C.; Teles, F.R.F.
Fanconi anemia (FA) is a rare genetic disease characterized by chromosomal instability and impaired DNA damage repair. FA patients develop oral squamous cell carcinoma (OSCC) earlier and more frequently than the general population, especially after hematopoietic stem cell transplantation (HSCT). Although evidence of an etiological role of the local microbiome and carcinogenesis has been mounting, no information exists regarding the oral microbiome of FA patients. The aim of this study was to explore the salivary microbiome of 61 FA patients regarding their oral health status and OSCC risk factors. After answering a questionnaire and receiving clinical examination, saliva samples were collected and analyzed using 16S rRNA sequencing of the V3-V4 hypervariable region. The microbial profiles associated with medical and clinical parameters were analyzed using general linear models. Patients were young (mean age, 22 y) and most had received HSCT ( n = 53). The most abundant phyla were Firmicutes [mean relative abundance (SD), 42.1% (10.1%)] and Bacteroidetes [(25.4% (11.4%)]. A history of graft-versus-host disease (GVHD) ( n = 27) was associated with higher proportions of Firmicutes (43.8% × 38.5%, P = 0.05). High levels of gingival bleeding were associated with the genera Prevotella (22.25% × 20%), Streptococcus (19.83% × 17.61%), Porphyromonas (3.63% × 1.42%, P = 0.03), Treponema (1.02% × 0.28%, P = 0.009), Parvimonas (0.28% × 0.07%, P = 0.02) and Dialister (0.27% × 0.10%, P = 0.04). Finally, participants transplanted over 11 y ago showed the highest levels of Streptococcus (18.4%), Haemophilus (12.7%) and Neisseria (6.8%). In conclusion, FA patients that showed poor oral hygiene harbored higher proportions of the genera of bacteria compatible with gingival disease. Specific microbial differences were associated with a history of oral GVHD and a history of oral mucositis.